An Exploratory Analysis of the Role of Higher Educationin Developing Knowledge Economy in Pakistan - Dr. Uzma Munawar; Dr. Muhammad Ayub Buzdar (Journal of Business & Tourism, 2021)
Knowledge is the key for growth and development of any country. Historically, only those countries succeeded and advanced which based their economies on knowledge. Higher education authorities in Pakistan are trying to promote the notion of knowledge economy in the country. This paper provides an exploratory analysis of various factors and indicators which disclose relationship between the higher education products and economic indicators of the country. There are four main pillars of knowledge economy i.e. education and training, information infrastructure, economic incentive &institutional regime, and innovation systems. Progress on different economic indicators is analyzed and concluded that investment in higher education is not supporting a shift in the nature of economy in Pakistan. Spontaneous and temporary steps may further deteriorate the situation. The paper urges on an overall restructuring of higher education policy and procedure of its implementation in contemporary economic and financial scenario of the country and globe.